Promotion of Local Economic Development (LED): experiences from rural community tourism - Hernández-Navarro, Juan Rafael (2012)
This article is a guide for the promotion of local economic development through community-based rural tourism. A methodological perspective for the accompaniment of organized communities interest- ed in the development of community rural tourism projects will be taken into consideration.The claim is to share a methodology applied in rural com- munities of Costa Rica and that it might be useful in similar situations.